Расчет потенциалов на каждом из отдельных взаимовлияющих заземляющих устройств - Нижевский, Илья Викторович; Гуль, Виктор Иванович; Нижевский, Виктор Ильич (НТУ "ХПИ", 2010)
Показано застосування нового способу вимірювання опору розтіканню складного ЗУ. За наслідками вимірювань запропонований розрахунок розподілу потенціалів в системі заземляючих пристроїв, що взаємно впливають один на другого. Показана необхідність таких розрахунків в умовах щільної забудови території.

Application of new method of measuring of resistance spreading of difficult is rotined grounding device. On results measurings the calculation of distributing of potentials is offered in the system of one another having effect of earthings devices. The necessity of such calculations is confirmed in the conditions of dense land development.
Keywords: ЗУ; сопротивление; мулевый потенциал; плотная застройка территории; опыты; подключение